The "Megapozitiv" Role of Enterprise Social Media in Enabling Cross-Boundary Communication in a Distributed Russian Organization. (January 2015) - Gibbs, Jennifer L.; Eisenberg, Julia; Rozaidi, Nik Ahmad; Gryaznova, Anna
Collaborating across boundaries is important for organizational innovation, but it poses a key challenge for large, distributed organizations. New technologies such as enterprise social media (ESM) are often heralded for their open infrastructure, democratic nature, and ability to break down traditional hierarchies and barriers to communication; thus, such tools may be expected to play a role in facilitating cross-boundary interaction. Usage patterns are likely to be shaped by existing cultural factors within the organizational and national contexts, however. Drawing on a case study of a large Russian telecommunications company, we empirically assess the introduction of an ESM application and the degree to which it promotes cross-boundary communication (across geographical and hierarchical lines), through analysis of server log data and in-depth interviews. Our findings demonstrate that ESM promotes cross-boundary communication, although there are distinct patterns for hierarchical and regional boundaries. Implications for ESM implementation and distributed collaboration are discussed.